Impact of a Virtual Reality-Based Simulation on Empathy and Attitudes Toward Schizophrenia - Marques, Antonio J.; Gomes Veloso, Paulo; Araújo, Margarida; de Almeida, Raquel Simões; Correia, António; Pereira, Javier; Queiros, Cristina; Pimenta, Rui; Pereira, Anabela S.; Silva, Carlos F. (Frontiers in Psychology, 2022)
Virtual Reality has been identified as one of the most promising resources for developing empathy towards stigmatized groups since it allows individuals to experience a situation close to reality from another person's perspective. This quasi-experimental study aimed to analyze the impact of a virtual reality program on promoting empathy towards individuals who have schizophrenia. The sample consisted of 102 higher education health students, distributed by the experimental and control groups. The program's impact was measured by completing several questionnaires regarding levels of empathy, attitudes, and knowledge about mental health. The results obtained revealed increased levels of empathy and more positive attitudes towards people with schizophrenia in the group exposed to the virtual reality environment. Thus, virtual reality could be an educational approach used to promote positive attitudes and empathy towards schizophrenia.